Telomere length analysis in amyotrophic lateral sclerosis using large-scale whole genome sequence data - Al Khleifat, Ahmad; Iacoangeli, Alfredo; Jones, Ashley R.; van Vugt, Joke J. F. A.; Moisse, Matthieu; Shatunov, Aleksey; Zwamborn, Ramona A. J.; van der Spek, Rick A. A.; Cooper-Knock, Johnathan; Topp, Simon; van Rheenen, Wouter; Kenna, Brendan; et al. (Frontiers in Cellular Neuroscience, 2022)
Amyotrophic lateral sclerosis (ALS), a neurodegenerative disease of motor neurons, is a complex genetic disease with heritability of 60%. Only about 14% of apparently sporadic ALS is explained by known genetic variation, suggesting that other forms of genetic variation are important, in addition to the known risk factors, male sex and increasing age. Telomeres maintain DNA integrity during cellular replication, differ between sexes, and shorten naturally with age. We find that longer telomeres are associated with ALS and specific phenotypic patterns of disease expression. We see the same pattern of telomere elongation in ALS in brain tissue. The association of longer telomeres with apparently sporadic ALS was also seen in people with familial ALS, supporting the notion that sporadic and familial ALS are not mutually exclusive categories but rather a spectrum.